STRUKTUR ORGANISASI PENUNJUK ARAH IMPLEMENTASI PROGRAM PEMBERDAYAAN MASYARAKAT MENUJU KEMANDIRIAN - Ipah Ema Jumiati (Universitas Sultan Ageng Tirtayasa, 2015)
Community empowerment as the main paradigm of good governance thatinvolves the State/Government, businesses and communities need a clear path in theimplementation of development programs through the clarity of the structure. Theorganizational structure is intended to divide all the tasks and functions of all membersof the organization that runs the appropriate authority of the duties and functions ofeach, in order to optimally achieve program objectives. Not stopping there, the clarityof the structure determines the success of policy implementation. With the structure, itcan be known who is doing what and how the flow goes organizational authority. Theresults show the organizational structure and work flow procedures of governmentbureaucracy in the implementation of PNPM Mandiri fragmented in terms of interagencycoordination, facilitator and program implementers. These circumstancesresulted in the throwing authority and responsibility because of the vagueness of theirroles, responsibilities and functions, resulting in inaccuracies in determining thequantity and quality of resources needed,